Diet and drinking habits in relation to the development of alcoholic pancreatitis. Issue 9 (September 1985) - Wilson, J S; Bernstein, L; McDonald, C; Tait, A; McNeil, D; Pirola, R C
Abstract : To determine whether increased intakes of fat and protein or particular drinking habits are associated with the development of alcoholic pancreatitis, a dietary study has been conducted. Patients with clinically evident alcoholic pancreatitis were compared with individuals with clinically evident alcoholic cirrhosis with respect to dietary and drinking habits before the onset of clinical illness. There was no significant difference between the two groups regarding intake of nutrients, drinking habits or type of alcoholic beverage consumed.